Landmark research for pulses improvement - Singh, R. J.; Chung, G. H. (The Indian Journal of Genetics and Plant Breeding, 2017)
This chapter reports that pulse crops (rich in protein) andcereals (rich source of carbohydrate) are an excellentcombination for balanced human diet. Crop rotation oflegumes with cereals enriches the soil because legumes fixnitrogen in soil in a symbiotic association with Rhyzobiumspecies. Pulse breeders have been confined to the primarygene pool (GP-1). Exploitation of secondary (GP-2) andtertiary (GP-3) gene pools for crop improvement is hamperedbecause of pre and post-zygotic barriers. National andinternational research institutes have conducted extensiveplant exploration to collect primitive cultivars, land races,and wild relatives before the spread of high yieldingvarieties and environmental destruction eliminates them.These invaluable materials are being deposited in mediumand long-term storage of gene banks. Breeders haveachieved substantial gain in the yield of pulse crops byconventional breeding by producing varieties that areresistant to abiotic and biotic stresses. Breeders haveproduced varieties with high protein content but withoutantinutritional elements. Roundup Ready 2 YieldÂ® soybean,produced through genetic transformation, hasrevolutionized the soybean production particularly in theUnited States. An example to exploit tertiary gene pool ofsoybean is shown. Such approach should be conductedfor other legumes to broaden their genetic base.